ENT530: Hippopo Baby Spa & Wellness / Nor Azila Azhar … [et al.] - Azhar, Nor Azila; Harun, Nadiatulnaim; Hidzir, Ummi Nadiera; Majid, Nur Nadira Nadia (2019)
Hippopo Baby Spa and Wellness is the first baby spa in Malaysia. Their first outlet started its operation at Centre point Bandar Utama, Petaling Jaya on 8th October 2013. From there, this business expended 6 outlets within a year and now Hippopo Baby Spa and Wellness have 13 total outlets in Malaysia. The major problem for this business is the awareness of parents about this baby spa. Some of parents taught that baby spa is expensive, so this make parents scared to send their child to baby spa. Some of the parent more prefer to send their child to swimming class, but they not aware that swimming class use chlorine water and that's not suitable for baby skin. Baby also love to massage so that they feel calm. In baby spa, their provide many of service for the babies.